2007
DOI: 10.1186/1471-2105-8-172
|View full text |Cite
|
Sign up to set email alerts
|

The CRISPRdb database and tools to display CRISPRs and to generate dictionaries of spacers and repeats

Abstract: BackgroundIn Archeae and Bacteria, the repeated elements called CRISPRs for "clustered regularly interspaced short palindromic repeats" are believed to participate in the defence against viruses. Short sequences called spacers are stored in-between repeated elements. In the current model, motifs comprising spacers and repeats may target an invading DNA and lead to its degradation through a proposed mechanism similar to RNA interference. Analysis of intra-species polymorphism shows that new motifs (one spacer a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

17
825
0
16

Year Published

2008
2008
2019
2019

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 902 publications
(878 citation statements)
references
References 24 publications
17
825
0
16
Order By: Relevance
“…In subsequent years similar CRISPR arrays were found in Mycobacterium tuberculosis 6 , Haloferax mediterranei 7 , Methanocaldococcus jannaschii 8 , Thermotoga maritima 9 and other bacteria and archaea. The accumulation of sequenced microbial genomes allowed genome-wide computational searches for CRISPRs (the first such analysis was carried out by Mojica et al in 2000 10 ), and the most recent computational analyses revealed that CRISPRs are found in ~40% of bacterial and ~90% of archaeal genomes sequenced to date 11,12 (Box 1).…”
Section: Brief History Of Crispr Researchmentioning
confidence: 99%
“…In subsequent years similar CRISPR arrays were found in Mycobacterium tuberculosis 6 , Haloferax mediterranei 7 , Methanocaldococcus jannaschii 8 , Thermotoga maritima 9 and other bacteria and archaea. The accumulation of sequenced microbial genomes allowed genome-wide computational searches for CRISPRs (the first such analysis was carried out by Mojica et al in 2000 10 ), and the most recent computational analyses revealed that CRISPRs are found in ~40% of bacterial and ~90% of archaeal genomes sequenced to date 11,12 (Box 1).…”
Section: Brief History Of Crispr Researchmentioning
confidence: 99%
“…The detailed information of CRISPRs was collected from CRISPR database (Grissa et al 2007a) for the genomes of extremophiles. Structural components including spacers, direct repeats (DRs) and CAS in the CRISPR loci were predicted by CRISPR Finder (Grissa et al 2007b) for those genomes whose information not availed in the CRISPR database. Appropriate location of cas genes was explored and identified from their genome maps in the KEGG database.…”
Section: Annotation Of Crispr Components At Genome-scalementioning
confidence: 99%
“…To identify more CAS proteins, sequences of P. gingivalis CAS that were annotated in the 35 genomes, as well as additional ones found in the NCBI protein database, were used to search against all the proteins annotated in the 35 genomes. Proteins that were not previously annotated as Mfa1 but with ≥90% identity and ≥90% length coverage to the queries were considered additional CRISPR-CAS proteins. e CRISPR: these are the number of CRISPR DNA sequences identified by the online CRISPRfinder programme (http://crispr.i2bc.paris-saclay.fr/Server/) [57]. …”
Section: Introductionmentioning
confidence: 99%
“… e CRISPR: these are the number of CRISPR DNA sequences identified by the online CRISPRfinder programme (http://crispr.i2bc.paris-saclay.fr/Server/) [57]. …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation